Bloom - Oppel, Kenneth, 1967- (Oppel, Kenneth, 1967- Overthrow, 2021)
After a mysterious rain, seeds sprout overnight into black grass that takes over everything in sight. Worse yet, they bloom and release toxic pollens, and even develop carnivorous pods that swallow animals and people. Anaya, Petra, and Seth, three teens living on Salt Spring Island near Vancouver, seem immune to the toxic plants and may be the only ones who can stop this invasion.